(untitled) (CIPEEX, 2023)
According to the Brazilian Institute of Geography and Statistics (IBGE), in 2019 there were more than 32 million elderly Brazilians. With the growing increase in the elderly population and life expectancy, there is a great concern in maintaining independence. This independence largely depends on maintaining physical fitness, which is necessary for performing daily life activities. According to Pillat et al. (2019), physical exercises have an impact on the physical, mental, and social health of the elderly, serving as a source of increased quality of life and a reduction or regression of the process of worsening frailty. The objective of this study was to analyze the level of satisfaction of elderly individuals who practice physical exercises. This is an exploratory descriptive study, of a cross-sectional nature, where the sample consisted of 27 elderly individuals (9 male and 18 female), aged between 60 and 81 years. For data collection, a questionnaire on sociodemographic information and a Life Satisfaction Scale were used. Regarding the domains of current satisfaction with overall life among elderly individuals who engage in physical activity, we observed a predominance of the "very satisfied" item in relation to the domains of Physical Health, Mental Health, and Social Engagement, while in the Physical Capacity domain, there was a predominance of the "extremely satisfied" item. In this way, regarding the data obtained, we can infer that physical activity exerts a strong influence on the feelings of improvement in physical and mental health, as well as the increase in social interaction.